AIT-S for Single-Machine Weighted Tardiness Problem - Kacper Petrynski; Iwona Pozniak-Koszalka; Leszek Koszalka; Andrzej Kasprzak (Vietnam Journal of Computer Science, 2019)
This paper concentrates on the newly improved algorithm for solving the single-machine total weighted tardiness (SMTWT) problem, called Algorithm Inspired by Tree and Sorting (AIT-S). The algorithm is based on searching the solution space along with the tree and sorting rules. The properties of the algorithm are studied taking into account the results of experiments made using the designed and implemented experimentation system. This system allows in tuning the parameters of the algorithm as well as to compare the effects obtained by AIT-S algorithm with effects of AIT algorithm, and known meta-heuristic algorithms. The paper shows that the proposed algorithm still requires some improvements, however, it seems to be promising.